Aging of tire and road wear particles in terrestrial and freshwater environments – A review on processes, testing, analysis and impact. (February 2022) - Wagner, Stephan; Klöckner, Philipp; Reemtsma, Thorsten
Abstract: The environmental fate of tire and road wear particles (TRWPs) receives increasing attention due to the per capita emission volumes of 0.2–5.5 kg/(cap year) and recent reports on the environmental hazard of TRWP constituents. It is expected that aging impacts TRWPs fate in the environment but detailed knowledge is quite limited, yet. Making use of information on tire aging, the available knowledge on environmental aging processes such as thermooxidation, photooxidation, ozonolysis, shear stress, biodegradation and leaching is reviewed here. Experimental techniques to simulate aging are addressed as are analytical techniques to determine aging induced changes of TRWPs, covering physical and chemical properties. The suitability of various tire wear test materials is discussed. Findings and methods from tire aging can be partially applied to study aging of TRWPs in the environment. There is a complex interplay between aging processes in the environment that needs to be considered in future aging studies. In addition to existing basic qualitative understanding of the aging processes, quantitative understanding of TRWP aging is largely lacking. Aging in the environment needs to consider the TRWPs as well as chemicals released. Next steps for filling the gaps in knowledge on aging of TRWPs in the environment are elaborated. Graphical abstract: Image 1 Highlights: Knowledge on tire aging is partially applicable to tire and road wear particles (TRWPs). Suitability of various TRWP test materials for aging studies is evaluated. Aging processes have a joint impact on TRWP properties and composition. Quantitative understanding of TRWP aging is lacking. Future research needs on TRWP aging are identified.